Isolation and Characterisation of Genes Encoding Ice Recrystallisation Inhibition Proteins (IRIPs) in the Cryophilic Antarctic Hair-Grass ( Deschampsia Antarctica ) and the Temperate Perennial Ryegrass ( Lolium Perenne ) - John, U. P.; Polotnianka, R. M.; Sivakumaran, K. A.; Mackin, L.; Kuiper, M. J.; Talbot, J. P.; Chew, O.; Nugent, G. D.; Cogan, N. O. I.; Drayton, M. C.; Forster, J. W.; Schrauf, G. E.; et al. (UKnowledge, 2023)
Antarctic hairgrass (D. antarctica Desv.), the only grass species indigenous to Antarctica, has a well developed tolerance of freezing, strongly induced by cold-acclimation. In response to low temperatures D. antarctica exhibits recrystallisation inhibition (RI) activity, localised to the apoplasm, that prevents further growth of ice crystals following freezing.